LINGUISTIK KOMPUTASI SEBAGAI DISIPLIN ILMU DAN RESPONS AKADEMIK DI LINGKUNGAN PERGURUAN TINGGI DI INDONESIA - Musthofa, Musthofa (Adabiyyāt: Jurnal Bahasa dan Sastra, 2022)
This paper describes an epistemological perspective of a new discipline in applied linguistics studies called "computational linguistics," the challenge and response faced by Indonesian linguists, and his problems in developing it. The analysis is carried out by utilizing epistemological concepts and theories, combined with Gianluca Carnabuci's theory called "knowledge hybridization" and the "challenge and response" theory proposed by Arnold J. Toynbee. The results show that epistemologically, computational linguistics has the validity to be called a scientific discipline. However, the response of Indonesian academics to its existence is still inadequate. This is related to the various challenges they face. For this reason, it is necessary to make multiple efforts to overcome it.